HIF1-alpha expression predicts survival of patients with squamous cell carcinoma of the oral cavity. - Marcelo dos Santos; Ana Maria da Cunha Mercante; Iúri Drumond Louro; Antônio José Gonçalves; Marcos Brasilino de Carvalho; Eloiza Helena Tajara da Silva; Adriana Madeira Álvares da Silva (PLoS ONE, 2012)
BACKGROUND: Oral squamous cell carcinoma is an important cause of death and morbidity wordwide and effective prognostic markers are still to be discovered. HIF1α protein is associated with hypoxia response and neovascularization, essential conditions for solid tumors survival. The relationship between HIF1α expression, tumor progression and treatment response in head and neck cancer is still poorly understood. PATIENTS AND METHODS: In this study, we investigated HIF1α expression by immunohistochemistry in tissue microarrays and its relationship with clinical findings, histopathological results and survival of 66 patients with squamous cell carcinoma of the lower mouth. RESULTS: Our results demonstrated that high HIF1α expression is associated with local disease-free survival, independently from the choice of treatment. Furthermore, high expression of HIF1α in patients treated with postoperative radiotherapy was associated with survival, therefore being a novel prognostic marker in squamous cell carcinoma of the mouth. Additionally, our results showed that MVD was associated with HIF1α expression and local disease relapse. CONCLUSION: These findings suggest that HIF1α expression can be used as a prognostic marker and predictor of postoperative radiotherapy response, helping the oncologist choose the best treatment for each patient.